A Mixed-Methods Evaluation of the #ifyougoigo Programme: A 10-Week Physical Activity Intervention for Women in Wales (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: The Torfaen Sports Development Team (Wales, United Kingdom) established the #ifyougoigo programme, whichseeks to leverage key facilitators, such as social support and companionship, to increase physical activity (PA) and physicalliteracy among women. The programme includes group-based exercise sessions, one-to-one personal training, educational workshops, and opportunities to try new sports. This research assessed the broad impact of the intervention and specifcally exploredthe relationship between physical literacy, companionship, and self-efcacy within the Self-Determination Theory framework.Methods: Women accepted onto the 10-week programme (n = 38, 41.5 ± 10.1 years) had their body mass, arm, thigh, andstomach circumferences, six-minute walking distance (sessional rate of perceived exertion recorded), National Health Service(NHS) resource usage, and device-based PA measured at four time-points. Furthermore, quality of life, perceived capability andwellbeing were measured using the EQ-5D and ICE-CAP surveys. Linear mixed regressions were used to assess the change fromthe pre- to post-intervention. Finally, participants also completed follow-up interviews (one-month post-programme) and focusgroups (six months post-programme), which were analysed thematically.Results: Quantitative measures did not indicate signifcant change, however promising trends in key variables were identifed.Downward trends in body mass (p = 0.091), body mass index (p = 0.091), and self-perceived anxiety and depression (p = 0.654);together with an increased sense of independence (p = 0.654), sense of achievement and progress (p = 0.654), and enjoyment andpleasure (p = 0.653) all indicate a positive programme impact trajectory at a larger scale. Qualitative fndings highlighted thatthe group exercise dynamic served as a vehicle for self-reﬂection, fostering emotional and social safety alongside enjoyment.Conclusion: The #ifyougoigo programme positively impacted women’s mental and physical health through group-based PA engagement. These fndings provide practical insights for the design and implementation of future community-based interventionsand can inform funding strategies to scale the programme to reach broader populations.Support/Funding Source: Torfaen County Borough Council